Dom Helder Camara: modelo de esperanca na caminhada para a paz e a justica social - Condini, Martinho (2004)
In this dissertation it is sought to show the actuation of Dom Hélder Pessoa Câmara, a model of hope in his tireless search for peace and social justice, in the north-east of Brazil, in Brazil as a whole, and in the World. It also highlights his important participation in the process of transformation of the Catholic Church from the second half of the twentieth century on. Before the realization of the Council Vatican II (1962-1965), the Catholic Church of Brazil started a process of renewal. This process of renewal of Brazilian ecclesiastic life took on greater visibility with the foundation of the National Conference of Bishops of Brazil (Conferência Nacional dos Bispos do Brasil0, the CNBB, on the 14th of October of 1952. If the Council Vatican II meant opening for the Church all over the world, much more for the Latin-American Church. The second and third General Conference of Latin-American Episcopate in Medellín (1968) and Puebla (1979) were a rethink of the teachings of the Council from the perspective of the Latin America, branded by poverty, social differences, and the repression imposed by the military regimen. Dom Hélder participated intensely in all this process of renewal of the Church and fight for human rights in the society. The dissertation reaps the hope that the actuation of Dom Hélder awakes inside and outside of the Church. Over the years, Dom Hélder became the mediator of hope, a prophet for the Church in Brazil